1987
DOI: 10.1172/jci113132
|View full text |Cite
|
Sign up to set email alerts
|

Transport kinetics of amino acids across the resting human leg.

Abstract: Flux rates of amino acids were measured across the leg after an overnight fast in resting human volunteers. A balanced amino acid solution was, after a primed infusion, continuously infused for 2 h at each of three step-wise and increasing rates corresponding to 83, 16.7, 33.2 Arterial steady state levels were obtained for most amino acids within 30 to 45 min after the primed constant infusion. Leg flux of amino acids switched from a net efflux after an overnight fast to a balanced flux between infusion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
3

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 26 publications
6
57
3
Order By: Relevance
“…In contrast, intravenous infusion by stepwise increased loads of amino acids to unselected patients and healthy volunteers indicated that amino acids themselves are involved in the process of initiation of translation (29), whereas carbohydrates and fat entirely lacked such effects (45). Also, there was no indication that glutamine alone had stimulatory effects in vivo in human muscles (46), while we observed that branched-chain amino acids stimulated human muscle protein synthesis, whereas insulin lacked this effect at physiological concentrations (32).…”
contrasting
confidence: 62%
“…In contrast, intravenous infusion by stepwise increased loads of amino acids to unselected patients and healthy volunteers indicated that amino acids themselves are involved in the process of initiation of translation (29), whereas carbohydrates and fat entirely lacked such effects (45). Also, there was no indication that glutamine alone had stimulatory effects in vivo in human muscles (46), while we observed that branched-chain amino acids stimulated human muscle protein synthesis, whereas insulin lacked this effect at physiological concentrations (32).…”
contrasting
confidence: 62%
“…Taurine residence time in muscle was estimated at 427 h in healthy men, nine times that of glutamine (29). The low fractional turnover of taurine might account for the slow isotopic equilibration, as it took 4 h of a constant infusion of [ 13 C 2 ]taurine to reach isotopic equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Because cataplerosis from TCA cycle is balanced with the inflow of carbon precursors (anaplerosis) (10), a higher glutamine flux would be expected in response to increased parenteral amino acid infusion. Lundholm and colleagues (23), in normal healthy adults, also showed an increased DGln across the leg in response to infusion of a balanced amino acid solution. A similar observation was made by Abumrad and colleagues (24) across forearm skeletal muscle during intravenous amino acid infusion.…”
mentioning
confidence: 88%
“…Although the above suggests skeletal muscle to be the major site for glutamine synthesis during amino acid infusion, it is not likely to be the predominant contributor. Studies in human adults show that only 25-30% of infused amino acid nitrogen is taken up by the skeletal muscle and 70% is removed by the splanchnic compartment (23,27,28). Thus, it is likely that the observed increase in Ra of glutamine in response to increased amino acid infusion is contributed by both the skeletal muscle as well as by the splanchnic organs.…”
mentioning
confidence: 99%